ZAWARCIE ZWIĄZKU MAŁŻEŃSKIEGO PRZED KONSULEM (WYBRANE ZAGADNIENIA) - Kremer, Andrzej (Zeszyty Prawnicze, 2017)
Contracting A Marriage before a Consul (Some Legal Aspects) Summary The possibility of being married before a consul has been created both by the regulations of international public law, particularly by the Vienna Convention on Consular Relations, as well as by the Polish law, including especially art 26 of the Act of the 13th Feb. 1984 on the Functions of a Consul of the Republic of Poland and art 1 § 4 of the Family and Guardianship Code as well as art. 60 of The Law on the Certificates of a Civil Status. These regulations entitle Polish citizens staying abroad to get married before a Polish consul. Nevertheless, they do not impose such a form of contracting a marriage. A man and a woman, who are Polish citizens staying abroad, can get married before a Polish consul or the other person designated to perform the functions of a consul. Such an opinion can be confirmed on the basis of current legal regulations. N obody doubted that art. 2 of the Family and Guardianship Code in its previous form confirmed that Polish citizens staying abroad could get married in accordance with lex loci celebrationis matrimonii being valid in the state of stay or before a Polish consul. It is always possible to choose between contracting a marriage according to the regulations of the state of stay before a local civil officer or before a consul. The only im portant condition for contracting a marriage before a consul is that it is not contrary to the laws of the state of stay of the people getting married.